2017
DOI: 10.1101/202440
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coupling of Polo kinase activation to nuclear localization by a bifunctional NLS is required during mitotic entry

Abstract: The Polo kinase is a master regulator of mitosis and cytokinesis conserved from yeasts to humans. Polo is composed of an N-term kinase domain (KD) and a C-term Polo-Box Domain (PBD), which regulates its subcellular localizations. The PBD and KD can interact and inhibit each other, and this reciprocal inhibition is relieved when Polo is phosphorylated at its activation loop. How Polo activation and localization are coupled during mitotic entry is unknown. Here we report that PBD binding to the KD masks a nuclea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Interestingly, a recent study identified a mechanism for nuclear localization of PLK1 where PBD binding to the kinase domain masks a nuclear localization signal in PLK1. Phosphorylation of the kinase domain within the T‐loop leads to exposure of an NLS causing the entry of PLK1 into the nucleus during G2 (Kachaner et al, ).…”
Section: Plk1‐scaffold Interactionsmentioning
confidence: 99%
“…Interestingly, a recent study identified a mechanism for nuclear localization of PLK1 where PBD binding to the kinase domain masks a nuclear localization signal in PLK1. Phosphorylation of the kinase domain within the T‐loop leads to exposure of an NLS causing the entry of PLK1 into the nucleus during G2 (Kachaner et al, ).…”
Section: Plk1‐scaffold Interactionsmentioning
confidence: 99%